2017
DOI: 10.1063/1.4983641
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced THz emission efficiency of composition-tunable InGaAs nanowire arrays

Abstract: We report the terahertz (THz) emission properties of composition-tunable, intrinsically n-type InGaAs nanowire (NW) arrays using THz time-domain spectroscopy. By tuning the alloy composition of In1-xGaxAs NWs from pure InAs (x(Ga)=0) up to the intermediate composition (x(Ga)∼0.5), a substantially enhanced (>3-fold) THz emission efficiency is found, which is ascribed to a reduction in electron accumulation at the NW surface and respective electron scattering at donor-type surface defects. These findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Surface accumulation and related electron scattering can be reduced by alloying InAs with gallium. The THz radiation from five Ga x In 1−x As NWs of different compositions is studied in [ 77 ]. It is found that the amplitude of THz pulses increases with increasing Ga fraction and reaches a maximum at x ≈ 0.47 ( Figure 20 a).…”
Section: Semiconductor Nanostructuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Surface accumulation and related electron scattering can be reduced by alloying InAs with gallium. The THz radiation from five Ga x In 1−x As NWs of different compositions is studied in [ 77 ]. It is found that the amplitude of THz pulses increases with increasing Ga fraction and reaches a maximum at x ≈ 0.47 ( Figure 20 a).…”
Section: Semiconductor Nanostructuresmentioning
confidence: 99%
“…THz excitation and photoluminescence spectra of Ga 0.47 In 0.53 As NWs ( b ). Reproduced from [ 77 ], with the permission of AIP Publishing.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Also THz emission may occur as a result of the boundary conditions on the carrier transport within a narrow-band semiconductor as a result of the photo-Dember (PD) effect [19], [20]. Recently THz emission has been observed in InGaAs nanowire arrays [21] as well as in iron-doped InGaAs [22].…”
Section: Introductionmentioning
confidence: 99%